Outcome of laminoplasty in cervical spinal cord injury with stable spine - Ghasemi, Amir Abbas (Asian J Neurosurg, 2016)
BACKGROUND AND OBJECTIVE: Cervical spinal cord injury (CSCI) with a stable spine has been increasing as the elderly population is dramatically increasing all over the world. In this study, we evaluated the neurological outcome of decompression surgery (laminoplasty) for these patients. MATERIALS AND METHODS: Forty-one patients with CSCI with stable spine who underwent decompression surgery (laminoplasty) were retrospectively studied. Inclusion criteria were as follows: CSCI without instability, spinal cord contusion in magnetic resonance image (MRI), spinal cord compression rate more than 20%, neurologic deficit American Spinal Cord Injury Association ([ASIA] scale from A to D), and follow-up of at least 12 months. Preoperative neurological state, clinical outcome, and neurological function were measured using the ASIA impairment scale, Japanese Orthopaedic Association (JOA) grading scale, and Hirabayashi recovering rate, respectively. RESULTS: Thirty-three (80.4%) patients showed improvement in ASIA grade at 12-month follow-up. Four (9.7%) patients in ASIA Grade A and 4 (9.7%) patients in ASIA Grade D remain unchanged. The mean JOA score improved from 8.4 ± 6.1 points preoperatively to 11.2 ± 5.4 points at 12 months postoperatively. Improvement in JOA was statistically significant (P < 0.05). The mean Hirabayashi recovery rate was 37.4 ± 25.3%. CONCLUSION: Surgical decompression (laminoplasty) is helpful in relieving cord compromise and neurological deficit in CSCI with stable spine.